Growth, characterization, and transport properties of ternary (Bi1−xSbx)2Te3 topological insulator layers. (17th October 2016) - Weyrich, C; Drögeler, M; Kampmeier, J; Eschbach, M; Mussler, G; Merzenich, T; Stoica, T; Batov, I E; Schubert, J; Plucinski, L; Beschoten, B; Schneider, C M; et al.
Abstract: Ternary (Bi1− x Sb x )2 Te3 films with an Sb content between 0 and 100% were deposited on a Si(1 1 1) substrate by means of molecular beam epitaxy. X-ray diffraction measurements confirm single crystal growth in all cases. The Sb content is determined by x-ray photoelectron spectroscopy. Consistent values of the Sb content are obtained from Raman spectroscopy. Scanning Raman spectroscopy reveals that the (Bi1− x Sb x )2 Te3 layers with an intermediate Sb content show spatial composition inhomogeneities. The observed spectra broadening in angular-resolved photoemission spectroscopy (ARPES) is also attributed to this phenomena. Upon increasing the Sb content from x = 0 to 1 the ARPES measurements show a shift of the Fermi level from the conduction band to the valence band. This shift is also confirmed by corresponding magnetotransport measurements where the conductance changes from n - to p -type. In this transition region, an increase of the resistivity is found, indicating a location of the Fermi level within the band gap region. More detailed measurements in the transition region reveals that the transport takes place in two independent channels. By means of a gate electrode the transport can be changed from n - to p -type, thus allowing a tuning of the Fermi level within the topologically protected surface states.